PERAN SERTIFIKASI GURU, NILAI KERJA DAN IKLIM SEKOLAH PADA KESEJAHTERAAN PROFESIONAL GURU (TEACHER'S PROFESSIONAL WELL BEING) PADA GURU SEKOLAH DASAR - Istiqomah Istiqomah; Wiwik Juwarini Prihastiwi (Jurnal Psikohumanika, 2021)
Abstract Improving the quality of education is carried out by increasing teacher professional well being. This study aims to determine the effect of teacher certification, work values ​​and school climate on teacher professional well being. The sampling technique used was accidental sample. The number of samples in this study were 61 teachers who had and had not received certification. The data analysis technique used multiple regression and t test. The results showed that there was an influence between work value and school climate on teacher professional well being, while perceptions of teacher certification did not have a significant effect. The contribution of the three variables is 69.2% and 30.80% is influenced by other factors. Each - each variable gave an effective contribution of 48.15% while the work value contributed 19.37%. Teacher professional well being, viewed from certified and uncertified teachers, does not show any difference. Teacher professional well being, viewed from the tenure of teachers who have worked for 20 years and less than 20 years, also does not show any difference. Key words: Teacher Certification, Work Value, School Climate, and teacher professional well being